Zinc phthalocyanine - Influence of substrate temperature, film thickness, and kind of substrate on the morphology - Schünemann, C; Elschner, C; Levin, A; Levichkova, M; Leo, K; Riede, M (Elsevier, 2011)
Zinc phthalocyanine (ZnPc), C32H16N8Zn, is a planar organic molecule having numerous optical and electrical applications in organic electronics. This work investigates the influence of various deposition parameters on the morphology of vapour thermal evaporated ZnPc films. For this purpose, ZnPc is deposited at different substrate temperatures up to 90 °C and film thickness up to 50 nm onto various substrates. The morphology of this ZnPc layers is characterised by X-ray diffraction (XRD), X-ray reflectivity (XRR) and atomic force microscopy (AFM) methods. XRD measurements show that all ZnPc films are crystalline in a triclinic (α-ZnPc) or monoclinic (γ-ZnPc) phase, independent from the kind of substrate, layer thickness, or substrate temperature. The ZnPc powder, the starting product for the thermally evaporated ZnPc films, is present in the stable monoclinic β-phase. Thus, the stacking of the ZnPc molecules changes completely during deposition. The crystallite size perpendicular to the substrate determined by XRD microstructure analysis is in the range of the layer thickness while the lateral size, obtained by AFM, is increasing with substrate temperature and film thickness. AFM and XRR show an increase of the layer roughness for thicker ZnPc layers and higher substrate temperatures during film deposition. The strain in the ZnPc films decreases for higher substrate temperatures due to enhanced thermal relaxation and for thicker ZnPc films due to lower surface tension. © 2011 Elsevier B.V. All rights reserved.